Acidified Infant Formulas with Probiotics: Application Relevance from the Position of Functional Nutrition - Evgeniya G. Makarova; Tatyana V. Klepikova; Sergei E. Ukraintsev; Olga K. Netrebenko ("Paediatrician" Publishers LLC, 2019)
Fermented milk products have functional properties which are useful for human health. Therefore this product group is frequently recommended for young children nutrition. Though until recently there were concerns among pediatricians about using of adapted acidified formulas instead of non-acidified. Modern data on administration efficiency and safety of adapted acidified formulas with probiotics is discussed, as well as functional effects of such formulas in infants are covered in this review.